Statistical analysis of agricultural soils climate data to aid food security under environmental change - Mitchell, Emily (2022)
Wheat is one of the most important food crops in the world for human consumption, livestock feed and biofuels. Demand for wheat has increased due to a rising population and crop growth concerns resulting from a changing climate. By exploring novel uses of data gathered on farming practices from the Farm Business Survey, this thesis aims to identify key farming practices which are most associated with high yields.